Entrepreneurship Management in the Digital Era for Micro, Small and Medium Enterprises in Indonesia - Azizah Shodiqoh Rafidah (International Journal of Economics, Business, and Entrepreneurship, 2024)
Digital transformation in the era of Industry 4.0 and Society 5.0 has fundamentally revolutionized business management, including Micro, Small and Medium Enterprises (MSME). In MSME management, there are several things that must be managed well, including financial management, human resource management, risk management, marketing management, production, development management and recovery management. These seven areas of management must be implemented in every business, including MSMEs. However, in general, MSMEs have not implemented management consistently and comprehensively. Utilizing e-commerce platforms, using digital marketing strategies, entrepreneurial management training, and developing unique local products are several ways that can be applied to increase the visibility and sales of MSME products in the digital market.